Proximate Composition, Bioactive Compounds, and Antioxidant Potential of Wild Halophytes Grown in Coastal Salt Marsh Habitats - Yasser A. El-Amier; Walid Soufan; Khalid F. Almutairi; Nouf S. Zaghloul; Ahmed M. Abd-ElGawad (Molecules, 2021)
Halophytes have been characterized as a potential resource for fiber, food, fodder, and bioactive compounds. Proximate composition, bioactive compounds, and antioxidant activity of five wild dominant halophytes (Arthrocnemummacrostachyum, Halocnemumstrobilaceum, Limoniastrummonopetalum, Limoniastrumpruinosum, and Tamarix nilotica) naturally growing along the Nile Delta coast were assessed. The soil supporting these halophytes was sandy to sand-silty, alkaline, with low organic carbon, and relatively high CaCO3. H. strobilaceum attained the highest moisture content, ash, crude fiber, lipids, and total soluble sugars. L. monopetalum showed the highest content of crude protein (18.00%), while T. nilotica had the highest content of total carbohydrates. The studied halophytes can be ranked according to their nutritive value as follows: H.strobilaceum > L.monopetalum > A.macrostachyum > L.pruinosum > T. nilotica. A. macrostachyum attained the highest amount of Na+, K+, Ca2+, and Mg2+. A. macrostachyum showed a high content of phenolic compounds, while H.strobilaceum was rich in tannins and saponin contents. The MeOH extract of A. macrostachyum and H. strobilaceum exhibited substantial antioxidant activity. The present results showed that the studied halophytes could be considered as candidates for forage production or used as green eco-friendly natural resources for bioactive compounds.